2005
DOI: 10.1080/14697010500143555
|View full text |Cite
|
Sign up to set email alerts
|

The production of trust during organizational change

Abstract: This paper investigates the relationships between organizational change and trust in management. It is argued that organizational change represents a critical episode for the production and destruction of trust in management. Although trust in management is seen as a semi stable psychological state, changes in organizations make trust issues salient and organizational members attend to and process trust relevant information resulting in a reassessment of their trust in management. The direction and magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 81 publications
4
107
0
7
Order By: Relevance
“…Many authors have identified organizational justice as a key ingredient in the development and decline of trust in management (e.g. Chory and Hubbell, 2008;Colquitt and Rodell, 2011) and change is one context that heightens perceptions of fairness (Hopkins and Weathington, 2006;Lines et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have identified organizational justice as a key ingredient in the development and decline of trust in management (e.g. Chory and Hubbell, 2008;Colquitt and Rodell, 2011) and change is one context that heightens perceptions of fairness (Hopkins and Weathington, 2006;Lines et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Certaines conditions doivent être rencontrées pour que le risque soit supporté et que la confiance se développe. Dans ce sens, nous rejoignons également les propos de Lines et al (2005) pour qui l'innovation constitue un contexte critique permettant de détruire ou de construire la relation de confiance. (2003) qui considèrent que tout changement affecterait la confiance à la baisse, notre étude démontre que la relation de confiance peut croître dans un contexte d'innovation.…”
Section: Discussionunclassified
“…Une expérience positive permet de confirmer que la confiance initiale est méritée, renforçant du même coup le niveau de confiance qui augmente au gré des interactions. Le changement organisationnel constituerait un contexte critique pour le développement ou la destruction de la confiance (Lines et al, 2005). Selon Morgan et Zeffane (2003), tout type de changement affecterait la confiance à la baisse, mais ces effets négatifs pourraient être contrebalancés par un processus participatif.…”
Section: La Relation De Confianceunclassified
See 1 more Smart Citation
“…The role of EI in workplace and leadership research has also been an important topic [5][6][7][8][9]. For instance, trust has been found positively related to job performance and negatively related to counterproductive behaviors, such as absenteeism or intentions to resign [10][11][12]. It has also been seen as an effective tool to counter the expectation of opportunistic behavior and to lower transaction costs [13].…”
Section: Introductionmentioning
confidence: 99%